Urgensi Pembentukan Undang-Undang tentang Majelis Permusyawaratan Rakyat - Harry Setya Nugraha (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2021)
This article aims to answer the urgency of the formation of Law about MPR in the Indonesian constitutional system. This research uses normative juridical research method with statutory and conceptual approach, as well as a qualitative descriptive analysis. This article concludes that 1) the formation of law on MPR has philosophical, juridical, and socio-political urgency; 2) the process of forming the law regarding the MPR must pay attention to the process and the content of the formation of good laws and regulations as regulated in the legislations.